Wife's Efforts in Earning a Family Livelihood in the Perspective of Maqashid Al-Syariah (Case Study in Soko Village, Tuban Regency, East Java) - Munir Munir; Farida Isroani (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The provision of maintenance in Islam is the responsibility of a husband. The provision of the husband's obligation to provide maintenance raises a new problem regarding the implementation of the wife working to meet the needs of the family. The purpose of this research is to evaluate the sharia values that exist in the case of women working for a living. The problem in this study is how women work to earn a living for their family needs in the view of sharia maqashid, what are the factors that affect women who work for a living, including: the factor of a sick husband, helping to prepare the future of the family and factors of helping the husband's income to meet the needs of the family and this can be justified by referring to the sharia maqashid. This study uses a descriptive research method using a qualitative descriptive analysis approach. The result of this study is that in a family husband and wife can play an equal role in the family, the wife plays the role of a breadwinner for her family because of various factors that cause the family's needs to not be met.